Wettability, reactivity, and interface structure in Mg/Ni system - S. Terlicka; N. Sobczak; Ł. Maj; P. Darłak; J.J. Sobczak (Journal of Magnesium and Alloys, 2024)
The sessile drop method was applied to the experimental investigation of the wetting and spreading behaviors of liquid Mg drops on pure Ni substrates. For comparison, the experiments were performed in two variants: (1) using the Capillary Purification (CP) procedure, which allows the non-contact heating and squeezing of a pure oxide-free Mg drop; (2) by classical Contact Heating (CH) procedure. The high-temperature tests were performed under isothermal conditions (CP: 760 °C for 30 s; CH: 715 °C for 300 s) using Ar + 5 wt% H2 atmosphere. During the sessile drop tests, images of the Mg/Ni couples were recorded by CCD cameras (57 fps), which were then applied to calculate the contact angles of metal/substrate couples. Scanning and transmission electron microscopy analyses, both coupled with energy-dispersive X-ray spectroscopy, were used for detailed structural characterization of the solidified couples.It was found that an oxide-free Mg drop obtained by the CP procedure showed a wetting phenomenon on the Ni substrate (an average contact angle θ < 90° in < 1 s), followed by fast spreading and good wetting over the Ni substrate (θ(CP) ∼ 20° in 5 s) to form a final contact angle of θf(CP) ∼ 18°. In contrast, a different wetting behavior was observed for the CH procedure, where the unavoidable primary oxide film on the Mg surface blocked the spreading of liquid Mg showing apparently non-wetting behavior after 300 s contact at the test temperature.However, in both cases, the deep craters formed in the Ni substrates under the Mg drops and significant change in the structure of initially pure Mg drops to Mg-Ni alloys suggest a strong dissolution of Ni in liquid Mg and apparent values of the final contact angles measured for the Mg/Ni system.